Study of relationship between umbilical cord blood hemoglobin percentage and perinatal asphyxia - ., Sambedna; Kumar, Amit; Chakore, Rita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Perinatal asphyxia may be caused by perinatal anemia. The pathophysiology and neurodevelopment effects are theoretically different from other causes of fetal asphyxia. Severe asphyxia can occur in infants around the time of birth by various reasons. The aim of this study to find the relationship between cord blood hemoglobin and perinatal asphyxia. Methods: This was a retrospective comparative study in department of OBG In tertiary care health centre. Umbilical cord blood samples were collected from 100 newborns with asphyxia at birth as study group and 100 newborns with non asphyxia as control group. Hemoglobin was measured colorimetrically. Results: This study finds that maximum number of patients in both the control and study group had hemoglobin in the range of 16.3-17.3 gm/dl. The difference was not statistically significant. P value>0.05. Conclusions: Hematological changes observed early after delivery can determine the duration of hypoxemia (acute versus chronic) Perinatal anemia causing moderate to severe perinatal asphyxia is associated with a higher risk for neonatal mortality. All survivors with perinatal anemia, however, showed no abnormalities in neurodevelopment in contrast to children who were born asphyxiated due to various another causes. The underlying pathophysiological mechanism for the favorable NDO in the perinatal anemia group needs further elucidation.